Information availability in the context of globai tendencies in Latvia - Gerkena, Vineta; Kalnina, Iveta; Pakalna, Daina (Knygotyra, 2003)
In view of current globalisation tendencies, every country is part of the world information space.In an information society, one of the main tasks is to promote welfare of the society by means of quality information services.There are three major preconditions that have to be observed for the performance of the new economic and social tasks:general availability of information;the ability to transform information into knowledge;issues related to the development of information services and their compatibility on a global scale.The e-Latvia programme is a socio-economic programme which seeks to find practical ways and possibilities for solving these tasks. The e-Latvia programme features ca. 30 state and local government sponsored projects. All of these groups of tasks apply to the sphere of libraries to a considerable degree.The State Unified Library Information System (SULIS) serves as a medium for co-operation among the information systems of libraries for:exchange of bibliographic information according to international standards which have been approved for use in the field;search, order, and receipt of information from Latvian and overseas libraries as well as other Internet information resources;a unified user interface for information search and document orders.Library activities in Latvia are regulated by the unified state policy in the field of libraries developed by the Ministry of Culture as well as by several national and international regulations.The Latvian system of libraries is formed of state, local government and private libraries.Libraries are divided into two types according to their functions: scientific and special libraries, and public libraries. One of the problematic issues concerning the use of electronic documents in libraries is the intensification of contradictions between general availability of information and barriers set by copyright. International forums are organised to discuss issues relating to the protection of intellectual property while retaining free access to information. The librarian community of Latvia is attempting to participate in discussions related to copyright issues which include the initiative taken by the National Library of Latvia in recent years.Formation and development of informational proficiency of users plays a fundamental part in the availability of information. The library is a place where such informational facilities can be mastered most efficiently.
Keywords: -